Simulated Casualty Evacuation Performance Is Augmented by Deadlift Peak Force. Issue 9 (2nd April 2019) - Poser, Whitney M; Trautman, Kara A; Dicks, Nathan D; Christensen, Bryan K; Lyman, Katie J; Hackney, Kyle J
Abstract: Introduction: The purpose of the current study was to examine if isometric peak force and rate of force development (RFD) were related to the ability to successfully perform a simulated casualty evacuation task in both unweighted and weighted conditions. Methods: Eighteen male participants from Army Reserve Officers' Training Corps (ROTC) completed a maximum isometric deadlift on a force plate (IRB#HE16227). Isometric peak force and RFD were calculated from ground reaction force. Two simulated casualty evacuation performance trials were then completed. The unweighted trial consisted of lifting and carrying a 75 kg dummy as quickly as possible for 50 m. The weighted trial was similar except 9 kg vests were added to both the simulation dummy and the participant to represent 18 kg of duty gear. Independent sample t -tests and Pearson correlations were performed to compare the characteristics of those who passed and failed the weighted trial. Results: All of the participants ( n = 18) completed the unweighted casualty evacuation trial, while 72% ( n = 13) were able to complete the weighted casualty evacuation trial. The participants that successfully completed the weighted evacuation trial had significantly ( p < 0.05) greater isometric peak force (1420 ± 165 vs. 1076 ± 256 N) and lean mass (74.18 ± 3.89 vs. 65.34 ± 3.89 kg) when compared to participants ( n = 5) that could not complete the weighted evacuating task trial. Additionally, greater Army Physical Fitness Test scores (288 ± 13 vs. 269 ± 16 arbitrary units) and significantly faster (30.34 ± 4.41 vs. 44.92 ± 10.62 seconds) unweighted evacuation trial times were observed in participants that could complete the weighted evacuation task. Peak force was also significantly correlated with lean mass ( r = 0.51, p < 0.05). There was no relationship between RFD and performance of the unweighted or weight trial. Conclusion: Isometric deadlift peak force represents an important determinant for the success of a simulated casualty evacuation task and may be a useful marker to include in periodic fitness evaluations of military personnel.